“Prevalence of NAFLD in Patients with Ischemic Heart Disease-A Study in Enam Medical College and Hospital in Bangladesh” - Parvez, Md Shahimur; Rahman, Mohammad Arifur; Lita, Arifin Islam; Hossain, Solaiman; Ahmed, Moeen Uddin; Ahmed, S Faisal; Ghosh, Tamal Peter (Jour Med Resh and Health Sci, 2021)
Background: Nonalcoholic fatty liver disease (NAFLD) has an in-creasing prevalence worldwide. It has also been closely associated with obesity and metabolic syndrome - two conditions known to be asso-ciated with ischemic heart disease (IHD). Several common metabolic risk factors contribute to development of both nonalcoholic fatty liver disease (NAFLD) and Ischemic Heart Disease worldwide with a preva-lence as high as 30% in the general population. Objective: To deter-mine prevalence of NAFLD in patients with Ischemic Heart Disease. Methods: The prospective study was conducted in the Department of Cardiology, Enam Medical College & Hospital, Savar, Bangladesh between January 2020 to December 2020. The study was conducted on 100 patients (62 patients with NAFLD and 38 Non-NAFLD) subjects were selected. Full history taking, clinical examination and laboratory tests including blood sugar, lipid profile and liver profile were done. Ultrasonography was performed to prove NAFLD while ECG and echocardiography were used for detection of myocardial ischemia. Results:The present study was by enrolling 100 patients of coronary artery disease divided into two groups i.e. NAFLD group n= 62 (62%) and Non NAFLD group n= 38 (38%). Participants were selected and divided into two groups; NAFLD group included 62 patients with ultrasonography NAFLD (45 males & 21 females) with mean age 45.81±12.46 years and non-NAFLD group of 38 subjects with mean age 45.32± 10.56 years. The present study shows that the prevalence of NAFLD was highest (86.8%) in more than 40 years of age group. The present study shows that the prevalence of NAFLD was more in males (84.2%) as compare to females (15.8%). The present study also shows significantly high incidence of metabolic syndrome in patients with NAFLD (23.7%) as compared to Non-NAFLD (3.2%) patients with Coronary Artery (CAD). Of the NAFLD group, the frequency of mild, moderate and severe NAFLD was 42.9%, 30% and 29.1% respectively. Subjects with NAFLD had a significantly higher BMI, waist circumference and weight compared to those of non NAFLD group (p=0.014, 0.0218 and <0.001 respectively). Independent risk factors for NAFLD were obesity, DM, high LDL, low HDL, waist circumference, glycated hemoglobin and IHD with odds ratios 1.09, 2.12, 1.01, 1.15, 1.13, 1.37 and 1.17 respectively. While independent risk factors for IHD included obesity, DM, high LDL, total cholesterol, triglycerides and the presence of NAFLD with odds ratios 1.31, 1.23, 1.19, 1.132, 1.68 respectively. Conclusion: The current study revealed that presence of NAFLD is associated with increased risk of IHD. This association was not only due to common risk factors shared between the two entities such as obesity, dyslipidemia and diabetes, but also a direct independent positive relationship was found between them. So NAFLD can be considered as an independent predictor of myocardial ischemia. The present study indicated a high prevalence of NAFLD in patients with documented Ischemic Heart Disease.